2020
DOI: 10.1029/2019jb019242
|View full text |Cite
|
Sign up to set email alerts
|

Amorphization and Plasticity of Olivine During Low‐Temperature Micropillar Deformation Experiments

Abstract: Experimentally quantifying the viscoplastic rheology of olivine at the high stresses and low temperatures of the shallow lithosphere is challenging due to olivine's propensity to deform by brittle mechanisms at these conditions. In this study, we use microscale uniaxial compression tests to investigate the rheology of an olivine single crystal at room pressure and temperature. Pillars with nominal diameters of 1.25 μm were prepared using a focused ion beam milling technique and were subjected to sustained axia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Here, the interest is on unravelling the mechanisms at the origin of the intragranular amorphous lamellae. Some evidence of shear lamellae resulting from stress-induced amorphization were recently reported in olivine in single crystals micropillars compressed at low temperature [32] or in shock recovered samples [9] but no information was provided regarding the deformation mechanism. The detailed observation in our specimen of the tip of a lamella interrupted inside the core of a grain provide novel information to elucidate the local amorphization mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the interest is on unravelling the mechanisms at the origin of the intragranular amorphous lamellae. Some evidence of shear lamellae resulting from stress-induced amorphization were recently reported in olivine in single crystals micropillars compressed at low temperature [32] or in shock recovered samples [9] but no information was provided regarding the deformation mechanism. The detailed observation in our specimen of the tip of a lamella interrupted inside the core of a grain provide novel information to elucidate the local amorphization mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The first report of amorphization of olivine has been made by Jeanloz et al [31] in shocked samples recovered from peak pressure of about 56 GPa (see also recent report of amorphization shear bands in shocked olivine from Zhao et al [9] ). The contribution of stress-induced amorphization to plastic deformation of olivine has first been reported in single crystal micropillars deformed in compression [32] at room pressure and temperature. Then Samae et al [30] reported pervasive occurrence of amorphization along grain boundaries in specimens deformed at low temperature, i.e.…”
Section: Introductionmentioning
confidence: 99%